Предмет: Математика,
автор: Asia1412
Пожалуйста.Срочно!!!!
Приложения:
Ответы
Автор ответа:
0
Використовуєм формулу коренів квадратного рівняння:
x1,2 = (4 ± √(4^2 + 4*7)) / 2
= (4 ± √36) / 2
= 2 ± 3
Тому, x1 = 2 + 3 = 5 та x2 = 2 - 3 = -1.
Далі робим обчислення значення виразу:
x2/1 + x2/2 = (-1)²/1 + (-1)²/2
= 1 + 1/2
= 3/2
x1,2 = (4 ± √(4^2 + 4*7)) / 2
= (4 ± √36) / 2
= 2 ± 3
Тому, x1 = 2 + 3 = 5 та x2 = 2 - 3 = -1.
Далі робим обчислення значення виразу:
x2/1 + x2/2 = (-1)²/1 + (-1)²/2
= 1 + 1/2
= 3/2
Похожие вопросы